Promoting Sustainability Through Green Chemistry, Part 1 - Paryjczak, Tadeusz (Problemy Ekorozwoju, 2008)
Green Chemistry is an important tool in achieving sustainability. The implementation of green chemistry, the design of chemical products and processes that reduce or eliminate the use and generation of hazardous substances, is essential if the expanding global populations to enjoy an increased standard of living without having a negative impact on the health of the planet. One of the major goods of sustainability is to maintain an optimal balance between increases in manufacturing output, and a clean and safe environment. Cleaner technologies will allow the chemical enterprise to provide society with the good and services on which it depends in an environmentally responsible manner. Green chemistry provides solutions to such global challenges as climate change, sustainable agriculture, energy, toxics in the environment and the depletion of natural resources. A collaborative effort by industry, academic and government is need to promote the adoption of the green chemistry technologies necessary to active a sustainable society.